2008
DOI: 10.1007/s00442-008-1204-x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of an extreme weather event and habitat fragmentation on a specialised insect herbivore

Abstract: Habitat fragmentation is considered to be one of the main causes of population decline and species extinction worldwide. Furthermore, habitat fragmentation can decrease the ability of populations to resist and to recover from environmental disturbances such as extreme weather events, which are expected to occur at an increasing rate as a result of climate change. In this study, we investigated how calcareous grassland fragmentation affected the impact of the climatically extreme summer of 2003 on egg depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 40 publications
3
67
3
1
Order By: Relevance
“…The interaction of habitat loss, fragmentation, and climate extremes will increase pressure on some populations and species, particularly in isolated trailing-edge populations where dispersal ability is limited (Travis 2003;Thomas et al 2004). For instance, Piessens et al (2009) found that for populations of Cupido minimus, a specialist herbivore butterfly, extinction probabilities were significantly higher for small populations in fragmented habitat during and after the hot summer in 2003 in Europe. Williams et al (2008) suggested that the first step towards conserving species in a changing climate is to understand the relative vulnerability of the species and implement known conservation techniques in potential refuge areas, including increasing habitat amount and connectivity.…”
Section: Drought-driven Change In Distribution and Numbers Wildlife Rmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of habitat loss, fragmentation, and climate extremes will increase pressure on some populations and species, particularly in isolated trailing-edge populations where dispersal ability is limited (Travis 2003;Thomas et al 2004). For instance, Piessens et al (2009) found that for populations of Cupido minimus, a specialist herbivore butterfly, extinction probabilities were significantly higher for small populations in fragmented habitat during and after the hot summer in 2003 in Europe. Williams et al (2008) suggested that the first step towards conserving species in a changing climate is to understand the relative vulnerability of the species and implement known conservation techniques in potential refuge areas, including increasing habitat amount and connectivity.…”
Section: Drought-driven Change In Distribution and Numbers Wildlife Rmentioning
confidence: 99%
“…Changes in environmental conditions, such as climate variability and loss of habitat, affect population dynamics, including dispersal ability, breeding success and mortality rates, and alter population density either temporarily or permanently (Fahrig 2003;Hughes 2003;Parmesan 2006). These changes can occur cyclically, with populations expanding or contracting as environmental conditions fluctuate, but if conditions alter too much, there may be more permanent effects on populations (Thomas et al 2006;Piessens et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Climate and point extremes may have substantial ecological and genetic effects, such as dramatic crashes or extinction of populations or species [11], genetic bottlenecks [12], substantial changes in age-and size-structure [13], changes in community structure and ecosystem functions [5,14], shifts in the phenology of plant and animal species [15] and species invasion [16]. However, there are often clear differences in the potential evolutionary consequences of climate and point extremes.…”
Section: Introductionmentioning
confidence: 99%
“…First, extreme events directly increase the risk of extinction by inducing massive mortalities [13]. In some cases, extreme events may be so severe that extirpation is inevitable in the absence of immigration.…”
Section: Introductionmentioning
confidence: 99%